Konseling Spiritual Teistik Melalui Penguatan Sikap Keagamaan untuk Membentuk Harmoni Hubungan Sosial (Studi Kasus Pada Peserta Didik MTs Negeri 4 Kota Tasikmalaya) - Alivia Zamzami Nur Maulida; Dudy Imanuddin Effendi; Sugandi Miharja (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2025)
This research aims to examine the role of theistic spiritual counseling in strengthening the religious attitude of students as well as its contribution in forming the harmony of social relations in MTs Negeri 4 Tasikmalaya City. This research uses a qualitative approach with analytical descriptive methods, which combines data collection techniques in the form of observation, in-depth interviews, and documentation to obtain a comprehensive picture of the implementation of theistic spiritual counseling in the school environment. The focus of the research includes the implementation of theistic spiritual counseling in strengthening religious attitudes, the impact of counseling services on changes in attitudes and social harmony of students, as well as supporting and inhibiting factors in the implementation of the counseling. The research results show that theistic spiritual counseling is effective in increasing the religious awareness of students, which then has a positive impact on their social behavior. A strong religious attitude contributes to the ability of students to control themselves, develop empathy, and build healthy communication with others, so that a harmonious social relationship is created in the school environment. The main supporting factor is the commitment and active role of BK teachers as well as the support of a religious school environment. While the hindering factors include the initial understanding of students who are still low about religious values and limited counseling infrastructure. This research contributes both theoretically and practically in the development of theistic spiritual guidance and counseling services in religiously labeled schools.